Peran Pemerintahan Daerah dalam Pengembangan Ekonomi Kreatif di Kabupaten Probolinggo - Ambarwati, Handika; Zubaidah , Siti; Laili, Rusdi; Basron, Basron; Fatiha, Emilda Sinar (Journal of Administration, Governance, and Political Issues, 2025)
The creative economy sector is the focus of economic growth in Probolinggo Regency, but there is no connectivity and equality with each other. Therefore, the role of the government must be maximized. The objectives of this study are (1) to emphasize the role of government in the development of the creative economy in Probolinggo Regency, (2) to investigate the factors that encourage and inhibit the development of the creative economy in Probolinggo Regency, and (3) to determine how local governments handle problems related to the development of the creative economy. Descriptive qualitative methods with quantitative data analysis were used in this study. The results of the analysis show that the government's function as (1) regulator, (2) catalyst, facilitator, and supporter, and (3) city supervisor is running well. In addition, the government's function as (4) consumer, investor, and even entrepreneur must be improved. Among the factors that encourage the development of the creative economy are the increase in the creative and digital sectors, the availability of the Probolinggo Regency Creative Economy Ecosystem Forum, the increase in domestic products, and the demographic bonus of the population. On the other hand, factors that hinder the development of the creative economy are the lack of facilities and start-up coaching, the less than optimal management of the Probolinggo Regency Creative Economy Ecosystem Forum, and the difficulty of getting creative products on the market. In Probolinggo Regency, the implementation of the creative economy is running quite well. However, improvements are needed to optimize the creative economy.